2020
DOI: 10.1002/ijfe.2255
|View full text |Cite
|
Sign up to set email alerts
|

Family ownership and M&A payment method

Abstract: We investigate the effects of family ownership on the choice between cash and stock payment in M&A operations. On a sample of 269 M&A transactions performed by Italian listed bidders over the period 2008-2015, we demonstrate that families are more inclined to pay in cash in order to avoid dilution. We also find that the influence of family ownership on the choice of the payment method is stronger for intermediate levels of control than for other levels. Furthermore, we document that financial structure conside… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 72 publications
0
2
0
Order By: Relevance
“…Alternatively, when family firms are acquirers, their valuation decisions are similar to non‐family firms or they pay slightly less (Haider et al, 2020; Leitterstorf and Wachter, 2016; Sraer and Thesmar, 2007; Thraya and Hamza, 2019). However, family firms are more likely to pay for assets with cash to preserve socioemotional wealth (Haider et al, 2020; Teti et al, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Alternatively, when family firms are acquirers, their valuation decisions are similar to non‐family firms or they pay slightly less (Haider et al, 2020; Leitterstorf and Wachter, 2016; Sraer and Thesmar, 2007; Thraya and Hamza, 2019). However, family firms are more likely to pay for assets with cash to preserve socioemotional wealth (Haider et al, 2020; Teti et al, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Prior research has identified method of payment decisions to be related to bidding company attributes including size, agency and governance environment, valuation, capital structure and ownership with cash more likely to be used as the acquisition method of payment if bidders are larger and have stronger governance structures, undervalued stock, greater financing flexibility, higher equity costs, and more concentrated and family ownership structures (Martin 1996;Rhodes-Kropf and Viswanathan 2004;Rossi and Volpin 2004;Faccio and Masulis 2005;Basu, Dimitrova, and Paeglis 2009;Martynova and Renneboog 2009;Teti, Dallocchio, and Currao 2020). Attributes of targets which are correlated with method of payment choice include firm size and relative target to bidder size, underlying risk and listing status (Chang 1998;Faccio, McConnell, and Stolin 2006;Capron and Shen 2007;Officer, Poulsen, and Stegemoller 2009;Boone, Lie, and Liu 2014;Huang, Officer, and Powell 2016) and acquisition-specific determinants of method of payment choice that have been identified include acquisition size, full or partial bid structure, bidder toeholds, and the industry match between bidding and target firms.…”
Section: Methods Of Payment Determinantsmentioning
confidence: 99%